Implementation Lean Manufacturing Method of Plywood Manufacture Company - Koh, Jastine; Singgih, Moses Laksono (Institut Teknologi Sepuluh Nopember, 2020)
The Plywood company in this study was able to produce 6,000m3/ year of plywood, but during 2018 and 2019 this company was only able to provide 2,905.14 m3/year and 1,120.73 m3/year. Production in 2018 and 2019 is far below the production capacity. This research will apply the lean manufacturing concept in the production process of a plywood company. This research uses value stream mapping (VSM), value stream analysis tools (VALSAT), process activity mapping (PAM), Pareto diagrams, and root cause analysis. It is found extreme categories that occur in many processes, namely processing production and inventory. The recommendations given are to reduce employees and provide adequate storage. The future state VSM shows that a change in a lead time of 68%, and the reduction of the production process is 248.18 minutes.Â Â